ANALYSIS OF SERVICE QUALITY OF BUILDING PERMIT (IMB) FOR SERVICE USERS: Case Study at the Semarang City Spatial Planning Office - Munawar Noor (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
IMB service quality must meet the aspects of tangibles, reliability,responsiveness, assurance (guarantee), and empathy. The purpose of this studywas to describe and analyze the quality of service to IMB permit service users (acase study on the Semarang City Spatial Planning Service). This type of researchwas qualitative with a research focus on IMB service quality covering aspects ofreliability, responsiveness, assurance, empathy, and tangibles. Researchinformants were determined based on purposive techniques (sampling aimed at the principle snowball). Data collection techniques were through in-depthinterviews, observation and documentation. Data analysis was carried outqualitatively with a model interactive model through the stages of datacollection, display data, data reduction and conclusion drawing. Researchconclusions: Analysis the quality of service for IMB permits to service users atthe Semarang City Spatial Planning Service was in accordance with applicableregulations. The delay in obtaining IMB permits was not due to the negligence ofservice personnel but due to the negligence of the IMB applicant in fulfilling theIMB requirements. Recommendations: Innovative steps are needed to intensifyimportant information and IMB requirements to service users through variousmedia up to the sub-district level, village